Absence of modulatory action on haptic height perception with musical pitch - Geronazzo, Michele; Avanzini, Federico; Grassi, Massimo (Frontiers in Psychology, 2015)
Although acoustic frequency is not a spatial property of physical objects, in common language, pitch, i.e., the psychological correlated of frequency, is often labeled spatially (i.e., “high in pitch” or “low in pitch”). Pitch-height is known to modulate (and interact with) the response of participants when they are asked to judge spatial properties of non-auditory stimuli (e.g., visual) in a variety of behavioral tasks. In the current study we investigated whether the modulatory action of pitch-height extended to the haptic estimation of height of a virtual step. We implemented a HW/SW setup which is able to render virtual 3D objects (stair-steps) haptically through a PHANTOM device, and to provide real-time continuous auditory feedback depending on the user interaction with the object. The haptic exploration was associated with a sinusoidal tone whose pitch varied as a function of the interaction point’s height within (i) a narrower and (ii) a wider pitch range, or (iii) a random pitch variation acting as a control audio condition. Explorations were also performed with no sound (haptic only). Participants were instructed to explore the virtual step freely, and to communicate height estimation by opening their thumb and index finger to mimic the step riser height, or verbally by reporting the height in centimeters of the step riser. We analyzed the role of musical expertise by dividing participants into non musicians and musicians. Results showed no effects of musical pitch on high-realistic haptic feedback. Overall there is no difference between the two groups in the proposed multimodal conditions. Additionally, we observed a different haptic response distribution between musicians and non musicians when estimations of the auditory conditions are matched with estimations in the no sound condition.